Peningkatan Gizi Keluarga melalui Kebun Sayur - Cita Eri Ayuningtyas; Septian Emma Dwi Jatmika; Raffika Yulianti (Universitas Mathla'ul Anwar Banten, 2020)
INCREASING FAMILY NUTRITION THROUGH HOME GARDENING. Stunting is one of a big health problem. Prevalence of the stunting in Indonesia based on Riskesdas 2018 was 12,8%, and compared to the number in Daerah Istimewa Yogyakarta was 20%. Problem solving for stunting can be started since pregnancy period such as fulfill the nutrition needs. A family should provide food that contain a good nutrition for their member family, especially for fiber from fruits and vegetables. A home gardening was a method for increasing dietary fiber in a family. The purpose of the activity was to increasing knowledge of housewifes in Gumulan how to fulfill nutrition needs from home gardening.The method used for identifying skill housewifes in home gardening. The ending of the activity housewifes could plant fruits and vegetables and make home gardening in their home.